Constitutional Justice in Circumstances of Public Authority Limits - Makogon, Boris V.; Markhgeym, Marina V.; Novikova, Alevtina E.; Nikonova, Lyudmila I.; Stus, Nina V. (Journal of History Culture and Art Research, 2018)
The article considers the bodies of constitutional justice as a significant subject of legal relations in the sphere of limited activity of public authority. The principle of separation of powers as universal is taken as a basis of classification. In modern states, the bodies of constitutional justice, exercising their special powers, are subject to limiting legal regulation, like any other public authority. The completeness and quality of functioning of various constitutional justice bodies guarantee the rule of law in the state. In addition to state-oriented tasks, the bodies of constitutional justice are an important link in the human rights system, ensuring the rights and freedoms of the individual. Within the framework of this work, the authors characterize the subjects of limiting legal relations taking a special place in the systems of state power bodies of the developed countries of the modern world.